تطوير المادة التعليمية بخريطة المفاهيم - Rina Dian Rahmawati (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2017)
The Mind Map of Understanding is a wonderful tool that helps the mind to think systematically. Is very simple. The mapping of concepts is the process and the method of entering the information into the mind, and to take information from the mind. The map became concepts in the area of learners' access to and development of information. The concept map allows for several purposes: examining what the student knew, learning how toteach, expressing non-concepts and evaluation. Keywords: Teaching Materials Development, Mind Map